Bis(3,5-dimethyl-4-vinylpyrazol-1-yl)acetic acid: A new heteroscorpionate building block for copolymers that mimic the 2-His-1-carboxylate facial triad - Türkoglu, Gazi; Ulldemolins, Cristina Pubill; Müller, Rainer; Hübner, Eike; Heinemann, Frank Wilhelm; Wolf, Marion; Burzlaff, Nicolai (European Journal of Inorganic Chemistry, 2010)
The new N,N,O ligand bis(3,5-dimethyl-4-vinylpyrazol-l-yl)-acetic acid. (Hbdmvpza) (4) suitable for copolymerisation was synthesised in a multi-step synthesis starting from bis(3,5-dimethylpyrazol-l-yl)methane (1). The κ -N,N,O facial coordination behaviour of 4 was verified by synthesis and characterisation of the tricarbonyl compounds [Mn(bdmvpza)(CO) ] (5) and [Re(bdmvpza)(CO) ] (6), the ruthenium bisphosphane complex [Ru(bdmvpza)Cl(PPh ) ] (7), as well as the complex [Cu(bdmvpza) ] (8). Copolymerisation of 4 with methyl methacrylate (MMA) or ethylene glycol dimethacrylate (EGDMA) led to solid phases P1a, P1b and P2 with different amounts of incorporated ligand 4. Furthermore, a homopolymer H1 of ligand 4 was successfully synthesised. Copolymer-bound manganese and rhenium tricarbonyl complexes P1a-Mn, P1a-Re, P2-Mn and P2-Re have been obtained by reaction of P1a and P2 with the metal precursors [MnBr(CO) ] and [ReBr(CO) ], respectively. The κ -N,N,O coordination of the manganese and rhenium centres was verified by IR spectroscopy and the amount of incorporated metal complex was determined by AAS or ICP-AES measurements. Treatment of the deprotonated copolymer P1a or P2 with copper(II) or iron(II) led to polymers P1a-Cu, P1a-Fe and P2-Fe. A bathochromic shift in the UV spectrum of P1a-Cu compared to the absorption maximum of the homogeneous complex 8 by 64 nm indicates copper centres with one ligand moiety bound only. AAS analysis of P1a-Fe and P2-Fe show that up to 64% of the ligand sites can be accessed with iron(II). Furthermore, two 2-oxocarboxylato complexes [Ru(bdmvpza)(BF)(PPh )] (9) (BF = benzoylformato) and [Ru(bdmvpza)(NOG)(PPh )] (10) (NOG = N-oxalylglycine) have been synthesised that mimic the shape of the active sites of 2-oxoglutarate dependent iron oxygenases. The successful copolymerisation of 9 and 10 with EGDMA was proven, by UV spectros py. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, We heim.